Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.17323/j.jcfr.2073-0438.13.2.2019.36-49
|View full text |Cite
|
Sign up to set email alerts
|

Do Political Connections Influence Investment Efficiency in Russian Companies?

Abstract: The question as to whether political influence can benefit the commercial activity of companies, and the relatedquestions surrounding political corruption that arise, are of perennial fascination for persons at every level of societyand in every country. With this in mind, this article seeks to explore the relationship between political connections incommercial firms and investment efficiency. This relationship will be studied on an empirical basis, and will shed somelight on the actual parameters, mechanisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
2
0
3
Order By: Relevance
“…These characteristics of the board modulate the relationship between earnings management and investment efficiency. Cherkasova and Ivanova (2019) showed that there is a significant relationship between political Communication and investment efficiency. Du et al (2018) showed that with increasing the integrity of governance, the problem of low investment decreases, and as a result, the efficiency of investment increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These characteristics of the board modulate the relationship between earnings management and investment efficiency. Cherkasova and Ivanova (2019) showed that there is a significant relationship between political Communication and investment efficiency. Du et al (2018) showed that with increasing the integrity of governance, the problem of low investment decreases, and as a result, the efficiency of investment increases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Victoria Cherkasova and Anna Ivanova argue that in Russia, political connections of chairmen of boards or CEOs lead to investment inefficiency. The reason is that state-related managers or directors try to achieve goals set by the government or power elite, which may not coincide with value maximization of the company [Cherkasova, Ivanova, 2019]. However, political ties of firms could be also value-enhancing, because of synergy between the government and the company.…”
Section: Randd and Ownership Structurementioning
confidence: 99%
“…wne.fa.ru введение Важнейшим структурным элементом экономической политики страны является инвестиционная деятельность банков. Исследование этой тематики привлекает интерес многих российских и зарубежных экономистов [1][2][3][4]. В России под инвестиционной деятельностью банков принято понимать совокупность мер, определяющих объем и структуру инвестирования с учетом приоритетных направлений [5].…”
unclassified
“…Привлекательность инвестиционной деятельности изучали А. В. Кравченко, Е. О. Коллегова [6]. По их мнению, это важный качественный критерий, который нужно учитывать при объективных предпосылках для инвестиций 1 . И. С. Самарин подчеркивает важность оценки инвестиционных проектов, поскольку часть проблем инвестирования возникает из-за некачественного выбора и подготовки проектов.…”
unclassified
See 1 more Smart Citation